Screening of Rabies among Dogs in Kelantan Using Direct Fluorescence Antibody Test (DFAT) - Dr.Fawzia Shalsh; Imad Ibrahim Ali Al-Sultana; Abdul Rahman Bin Azizc; Salahudeen Muhamad Muhamad (Al-Qadisiyah Journal of Pure Science, 2021)
Inarguably, in several developing and in-transition countries, human are threatened by the occurrence of rabies in domestic dogs and it is posing a major concern. However, the infection of rabies in domestic livestock could definitely have economic consequences. This study aimed to determine the occurrence of rabies among dogs in Kelantan by the use of Direct Fluorescent Antibody Test (DFAT) to determine presence of rabies infection in dogs. The detected rabies cases were 12.5% (1 out of 8 samples). The finding might be inconclusive due to small sample size. It was generally difficult to obtain a satisfactory large number representing high sample size. The positive control used in this research work is made up of inactivated rabies vaccine (Rabisin®) whose antigenic determinant is the viral glycoprotein. It was sufficient to be used although the use of live rabies virus for inoculation in brain tissue smear would be a better option for positive control. The finding from the florescence microscopy examination reveals a good brilliant green fluoresce of high grade (+4) for the positive control. The results of the samples show all negative at conjugate dilution 1:100.